2012
DOI: 10.1080/03602559.2012.654575
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrochemical Behaviors and Anion Recognition of A Novel Star-[Polystyrene-b-poly(ferrocenyloxy ethyl acrylate)]6with Hexafunctional Cyclotriphosphazene Core

Abstract: A novel star-[polystyrene-b-poly(ferrocenyloxy ethyl acryl ate)] 6 with hexa-functional cyclotriphosphazene core (star-(PS-bPFcEA) 6 ) was synthesized by atom -transfer radical polymerization(ATRP) and its electrochemical behaviors and anion recognition was investigated through CV. The results indicated that increasing of molecular weight resulted in obvious decreasing of reduction peak potential E pc , and the oxidation peak potential E pa kept comparatively stable. Moreover, when titrating anion H 2 PO À 4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…They concluded that the introduction of phenol groups via the nucleophilic aromatic substitution reaction of aryl fluorides with K 2 CO 3 afforded a very low-cost and efficient alternative to demethylation of the methoxy groups using either pyridine hydrochloride or BBr 3 when a large excess of reagent is used. The yields and selectivity of the reactions were also improved significantly utilizing the nucleophilic aromatic Gong et al [173] synthesized and characterized an ABB 0 -type monomer containing a pair of phenolic groups and an aryl fluoride, which was activated toward displacement by the attached oxazole ring. The ABB 0 monomer (1-34, Scheme 12) was self-condensed to form a hb poly(aryl ether oxazole) (hb-PAE-Ox) with terminal phenolic groups.…”
Section: Hyperbranched Poly(aryl Ether)s With a Phosphine Oxide Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the introduction of phenol groups via the nucleophilic aromatic substitution reaction of aryl fluorides with K 2 CO 3 afforded a very low-cost and efficient alternative to demethylation of the methoxy groups using either pyridine hydrochloride or BBr 3 when a large excess of reagent is used. The yields and selectivity of the reactions were also improved significantly utilizing the nucleophilic aromatic Gong et al [173] synthesized and characterized an ABB 0 -type monomer containing a pair of phenolic groups and an aryl fluoride, which was activated toward displacement by the attached oxazole ring. The ABB 0 monomer (1-34, Scheme 12) was self-condensed to form a hb poly(aryl ether oxazole) (hb-PAE-Ox) with terminal phenolic groups.…”
Section: Hyperbranched Poly(aryl Ether)s With a Phosphine Oxide Moietymentioning
confidence: 99%
“…Changing Polymer Solvation by Electrochemical Means: Basics and Applications polymers with block arms act similarly [173]. Apparently, the organic spacers assure solubility in organic media in both oxidation states, which allows the determination of the hydrodynamic radii by electrochemical means.…”
Section: Metallocenesmentioning
confidence: 99%
“…The electrochemical behaviours of some ferrocene derivatives were investigated by cyclic voltammetry showing interesting behaviour [34,37,38], this encouraged us to study the electrochemical behaviour of some new polyazomethines with ferrocene moiety in the main chain. The electrochemical redox properties of the newly synthesized polyazomethines 6a-e based ferrocene moiety were studied by cyclic voltammetry at room temperature in (dry CH 2 Cl 2 : absolute ethanol, 1 : 1) solutions, using glassy carbon electrode as working electrode, Pt gauze as a counter electrode and Ag/AgCl as a reference electrode, and tetra-n-butylammonium perchlorate (TBAP) as the supporting electrolyte.…”
Section: Electrochemical Studymentioning
confidence: 99%
“…[1][2][3] Ethylene is the simplest and most inexpensive olefin monomer, block polyolefin such as dendritic-linear block polymers, hyperbranched-linear polymers, and star-linear polymers, produced from ethylene alone is favorable for commercial utility. [1,2] For unique chain architectures, block polyelfin is readily amenable for applications as thermoplastic elastomers, compatibilizers, drug support, and high-impact plastics for its unusual compatibility, solubility, and solid-state properties.…”
Section: Introductionmentioning
confidence: 99%